Development of a new common tobacco cultivar resistant to mosaic virus in Brazil - Pontes, Oscar F. Swenson; Espindola, Edson S.; Cavagnollo, Erceli M.; Sudo, S. (Pesquisa Agropecuaria Brasileira, 2014)
A new "Galpão Comum" tobacco variety carrying resistance to the Tobacco Mosaic Virus - TMV, was developed through the backcross metbod. The initial crosses employed the most commercial CO-D (Palotina) variety and the donor parente Ky- 14 and Ky-12 that are Burley varieties and also belong to the air cured group. These donor parents possess the hypersensitivity (HS) type of resistance to TMV. The resultant TMV immune variety, named CSC 300, was higher in yield and had more desirable cured leaves, according to the amount of tanish leaves (L) and quality grade 2 produced. The phenotypic characteristics of this new variety were considered quite similar to the recurrent parent (CO-D/Palotina). The smoking panels tests were very good and had a strong agreement with the normal characteristics for the "Galpão Comum" favorite type. This new variety was developed to be given to the formers, for the 1986/87 crop season, by the Genetic and Breeding Research Center of Souza Cruz.